Effectiveness of Calcium Carbonate in Chicken Eggshell as a Copper Adsorbent in Kotagede Silver Craft Liquid Waste - Karroghi, Silmi Aziza; Nurjazuli, Nurjazuli; Joko, Tri (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2024)
The silver craft industry’s liquid waste contains hazardous heavy metals such as Cu. Waste containing Cu is directly discharged into the environment, harming the environment and living organisms. An alternative treatment for this liquid waste is the adsorption method using activated chicken eggshells, which have a high CaCO3 content as an adsorbent. This study aims to determine the effectiveness of chicken eggshell adsorbents in reducing Cu levels in silver craft liquid waste solutions. The research employs a quasi-experimental method. The dependent variable in this study is the Cu content in the silver craft liquid waste. In contrast, the independent variables are adsorbent particle size with variations of 50 mesh, 100 mesh, and 150 mesh and adsorbent concentrations with variations of 30 g/L, 40 g/L, and 50 g/L. The statistical test used is the General Linear Model (GLM). The results showed that eggshell adsorbents could reduce Cu levels by 80.82% (from 2.671 mg/L to 0.512 mg/L), which occurred in the particle size group of 150 mesh and a concentration of 40 g/L. However, this result has yet to effectively reduce Cu levels below the standard (0.5 mg/L) stipulated by DIY Regional Regulation No. 7 of 2016. Data analysis with the GLM test showed a significant difference in Cu levels based on variations in adsorbent particle size (p-value=0.000) and adsorbent concentration (p-value=0.024). The interaction between particle size and adsorbent concentration did not show a significant difference (p-value=0.810), indicating it did not reduce Cu levels effectively.